Effects of Electrical Stimulation on Stem Cells - Heng, Wang; Bhavsar, Mit; Han, Zhihua; Barker, John H. (Current Stem Cell Research & Therapy, 2020)
Recent interest in developing new regenerative medicine- and tissue engineering-based treatments has motivated researchers to develop strategies for manipulating stem cells to optimize outcomes in these potentially, game-changing treatments. Cells communicate with each other, and with their surrounding tissues and organs via electrochemical signals. These signals originate from ions passing back and forth through cell membranes and play a key role in regulating cell function during embryonic development, healing, and regeneration. To study the effects of electrical signals on cell function, investigators have exposed cells to exogenous electrical stimulation and have been able to increase, decrease and entirely block cell proliferation, differentiation, migration, alignment, and adherence to scaffold materials. In this review, we discuss research focused on the use of electrical stimulation to manipulate stem cell function with a focus on its incorporation in tissue engineering-based treatments.
Keywords: stem cells